Prenatal Diagnosis of Umbilical Cord Ulcer: A Report of Two Cases - Daisuke Katsura; Suzuko Moritani; Shunichiro Tsuji; Kaori Hayashi; Kazutaka Yamada; Shinsuke Tokoro; Kounosuke Suzuki; Fuminori Kimura; Takashi Murakami (Case Reports in Obstetrics and Gynecology)
Umbilical cord ulcer is related to fetal intestinal atresia or meconium; perforation of the ulcer causes fetal deterioration leading to fetal and neonatal death owing to fetal hemorrhage. However, to the best of our knowledge, a method to diagnose umbilical cord ulcer prenatally is not available. No reports exist about the prenatal findings before perforation of umbilical cord ulcer using ultrasonography. We encountered two cases of umbilical cord ulcer showing ultrasonographic finding of a linear echo around the umbilical cord. Umbilical cord ulcers with an exposed umbilical cord artery in the first case and with perforation of the artery in the second case were diagnosed postnatally. When we encounter such ultrasonographic finding, especially with polyhydramnios and high amniotic bile acid concentration in cases of fetal intestinal atresia, risk of perforation of the umbilical cord ulcer should be included in the differential diagnosis.